Patterns of Drug Utilization and Self-Medication Practices: A Cross Sectional Study - Hamod Al-Omrani; Mandeep Kaur Marwah; Razan Al-Whaib; Mohammed Mekkawy; Hala Shokr (Pharmacy, 2023)
Background: Self-medication (SM) is a growing phenomenon worldwide that has recently been classified as one of the most serious public health problems. SM can result in an incorrect self-diagnosis, inappropriate treatment, potential adverse reactions, interactions, and the masking of more sinister disease. Objectives: To assess the prevalence of SM practices amongst healthcare professionals and the general population in Saudi Arabia and to identify the sociodemographic contributing factors to this practice. Methods: A total of 540 participants were enrolled in this study. Participants were asked to complete the study questionnaire comprising two sections to gather demographic information and to collect data regarding SM practice. Results: The prevalence of SM practice among the study participants was 78.6%, and it was the highest among the middle age groups of (21–40 years) 82% compared to the younger and older age groups. The observed prevalence was higher in the female participants (53.7%) and those who live alone. Type of education did not affect the attitude of SM (p = 0.374); however, level of education strongly affected the prevalence of the SM, with higher incidence among university graduates (p < 0.001). Analgesics with antipyretics properties were the most self-medicated drugs. Patients considering their illnesses minor was the main reason behind the high prevalence of this practice. Among healthcare professions the highest prevalence of SM was found among pharmacists (95%), followed by physicians, nurses, and other medical practitioners. Conclusion: The general population should be better educated and made conscious about the consequences, risks, and side effects of SM. Awareness campaigns may prove to be useful in this matter, allowing the patient to consider the appropriateness of this practice. Individuals in the age group of 21–40 years, females, and those who live alone should be considered priority target populations in the design and implementation of SM awareness projects.